Factors associated with overcrowded pediateric emergency rooms in Northern India and possible solutions: a medical school setting - Saqib, Najmus; Qazi, Mahvish (International Journal of Contemporary Pediatrics, 2019)
Background: To quantify the extent of emergency department overcrowding in a tertiary care hospital and to identify possible solutions. Methods: A retrospective hospital record-based study was conducted at Government Medical College Jammu, Jammu and Kashmir, India from the Department of Pediaterics and comprised data of all the patients presenting to the emergency department between 1st January 2018 to 31st December 2018. Demographic characteristics, length of stay (LOS), revisit frequency and consultation status of the patients were determined. Results: Of the 1,17,035 patients, 25,223 (43.89%) were discharged straight away while 24,113 (41.95%) were admitted to different wards and subspecialties. Besides, 6464 (11.25%) patients left the department against medical advice, 861 (1.5%) expired, 741 (1.29%) were referred to other hospitals and 67 (0.12%) were dead on arrival. Of those who were admitted, 1,4498 (60.13%) patients stayed for more than 10 hours before getting the main hospital bed. Mostly, the delays observed were due to delay in getting lab reports, already preoccupied ventilators and incubators in pediatric and neonatal intensive care units, not using checklist for proper reassessment of patients and early discharge, overburdened by patients coming in just for nebulization and intravenous or intramuscular medications, the admitting residents detain the unstable patient longer in emergency department before admission to wards. Conclusions: In conclusion, cooperation of the managers, relevant departments and a multidisciplinary approach are necessary to achieve the goals to reduce overcrowding in the emergency departments.